Epidemiological aspects of endoscopic resections of colorectal polyps in patients at an endoscopy training center in the Santos region, Brasil - Vilela Filho, Tiago Franco (2017)
Introduction: Colorectal polyps are structures that project from the surface of the mucosal layer of the large intestine. They are classified as neoplastic or non-neoplastic. Early detection of pre-neoplastic lesions is important for preventing colorectal cancer. These can be resected so as to decrease the morbidity and mortality rates. Colonoscopy is the gold-standard procedure for diagnosing and resecting precursor lesions. Objective: To evaluate the epidemiological, endoscopic and histological aspects of endoscopic resection of lesions of the colon and rectum at a training center. Materials and method: A search was conducted in the database of our institution covering the period from January 2011 to July 2014. Cases that underwent endoscopic resection of polyps and/or colorectal lesions were selection. The following variables were defined: general data on the patients (age, gender and indication from the examination) and data on the polypoid lesion (number, histological type and topographic distribution). Results: 678 lesions were identified in 456 examinations. Regarding sex, 242 (53.1%) were female and 214 (46.9%) were male. The mean age was 64.54 years, with extremes of 5 and 94 years. The most frequent locations were the rectum (21%) and sigmoid (20%). Histologically, 34.7% were hyperplastic polyps and 58.9% were adenomatous polyps, of which 74.1% were tubular, 10.6% tubulovillous, 2% villous and 13% indeterminate; and 1.7% were adenocarcinomas. In 65.4% of the cases, the examination showed that only one polyps was present, while 34.6% had two or more lesions. Conclusion: In our clinic, with a mean of 250 examinations/month, the parameters evaluated were compatible with the results reported in the literature.